Constraint Analysis by Faculty of SAUs for Strengthening Organizational Climate in Karnataka (Indian Journal of Extension Education, 2023)
The study aimed to evaluate the perception of faculty members towards the organizational climate by evaluating the constraints and finding the suggestions in three colleges, namely UAS Dharwad, UHS Bagalkot, and KVAFSU Bidar, during the academic year 2020-2021 in Karnataka. The researchers used a pre-set scale consisting of 32 items that represented six organizational climate characteristics, viz. communication, supervision, decision-making, motivation, guidance, and organization management. A total of 135 faculty members participated in the study, and personal interviews were conducted to collect the data. The results revealed that the majority of faculty members faced challenges such as poor workplace relations, lack of motivation and appreciation for their achievements, improper communication of work-related information, and lack of guidance from superiors in difficult situations that hampered the organizational climate. To foster a cordial climate within the organization, faculty members suggested fostering friendly relationships among faculty and building trust, the head’s encouragement for good deeds, reward and incentive programs, and weekly faculty group meetings were suggested to increase motivation and appreciation for achievements.